2021
DOI: 10.1093/sysbio/syab050
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Species Delimitation Methods in Radiations: The Land Snail Albinaria cretensis Complex on Crete

Abstract: Delimiting species in radiations is notoriously difficult because of the small differences between the incipient species, the star-like tree with short branches between species, incomplete lineage sorting, and the possibility of introgression between several of the incipient species. Next generation sequencing data may help to overcome some of these problems. We evaluated methods for species delimitation based on genome-wide markers in a land snail radiation on Crete. Species delimitation in the Albinaria cret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…The PTP approach (Zhang et al, 2013) subdivided the Siphonaria data set also into a quite high number of primary species hypotheses (89). Overestimations of the number of species by these tree-based approaches have also been observed in several other empirical studies (Bamberger et al, 2022;Puillandre et al, 2021;Sauer & Hausdorf, 2012;Talavera et al, 2013). Thus, the over-splitting by these approaches can probably not be exclusively attributed to badly reconstructed trees in the case of our Siphonaria data set.…”
Section: Siphonaria Speciessupporting
confidence: 74%
“…The PTP approach (Zhang et al, 2013) subdivided the Siphonaria data set also into a quite high number of primary species hypotheses (89). Overestimations of the number of species by these tree-based approaches have also been observed in several other empirical studies (Bamberger et al, 2022;Puillandre et al, 2021;Sauer & Hausdorf, 2012;Talavera et al, 2013). Thus, the over-splitting by these approaches can probably not be exclusively attributed to badly reconstructed trees in the case of our Siphonaria data set.…”
Section: Siphonaria Speciessupporting
confidence: 74%
“…(2020) analyzed 99 population pairs in the genus Drosophila and found that bpp identified 80 pairs as distinct species, whereas reproductive isolation was identified in only 69 pairs. Similarly, Bamberger et al . (2022) examined 48 Albinaria cretensis land snail populations, and found that morphological classifications suggested 3–9 species while bpp suggested 45–48.…”
Section: Introductionmentioning
confidence: 68%
“…For example, Campillo et al (2020) analyzed 99 population pairs in the genus Drosophila and found that bpp identified 80 pairs as distinct species, whereas reproductive isolation was identified in only 69 pairs. Similarly, Bamberger et al (2022) examined 48 Albinaria cretensis land snail populations, and found that morphological classifications suggested 3-9 species while bpp suggested 45-48. Barley et al (2018) simulated multiple populations from a single species that exhibits population structure and isolation by distance, and found that bpp delimits geographically separated populations as distinct species.…”
Section: Introductionmentioning
confidence: 99%
“…They have been applied to a wide range of systems, in particular as a validation method in integrative species delimitation analyses (e.g. Bacon et al, 2012;Bamberger et al, 2022;Carstens et al, 2013).…”
Section: Ta B L Ementioning
confidence: 99%